Class assemblies and self-ethics through Edgar Morin’s perspective - Tordin, Denise Cristina (2022)
This article analyzed a school's class assemblies from Edgar Morin's ethics perspective. How are class assemblies organized at Municipal Secondary Schools in Campinas/SP? How can they contribute to the understanding of ethics in the school environment? This research employed qualitative methods of interviews and observation. The results show that introductory activities to class assemblies - such as reading, music, and physical contact - develop self-knowledge, reduce hostilities and awaken recognition of the other. The study contributes to the reflection on conflict resolution in the school environment. It also contributes to understanding how conflict can be an opportunity for more mature social relations.